2015
DOI: 10.7314/apjcp.2015.16.13.5297
|View full text |Cite
|
Sign up to set email alerts
|

Trends and Analysis of Cancer Incidence for Common Male and Female Cancers in the Population of Punjab Province of Pakistan during 1984 to 2014

Abstract: , and non-Hodgkin lymphoma (NHL, 9.53%) were found to be the highest in male patients, whereas breast cancer (46.7%), ovary tumors (6.80%), and cervix (6.31%) cancer incidence rates were observed to be the most common in female patients. The age range distribution of diagnosed and treated patients in conjunction with the percentage contribution of cancer patients from 15 different cities of Punjab province treated at the Institute of Nuclear Medicine and Oncology, Lahore are also included. Leukemia was found t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 38 publications
1
21
0
Order By: Relevance
“…This is the reason why we found that after breast cancer, the most commonly reported cancer was head and neck which are strongly linked to consumption of smokeless tobacco. This was also reported previously from registry of province of Punjab, Pakistan [18].…”
Section: Discussionsupporting
confidence: 88%
“…This is the reason why we found that after breast cancer, the most commonly reported cancer was head and neck which are strongly linked to consumption of smokeless tobacco. This was also reported previously from registry of province of Punjab, Pakistan [18].…”
Section: Discussionsupporting
confidence: 88%
“…Variations in the cancer data obtained from various studies conducted in different parts of the country are shown in Table 1 and appear to be quite marked and significant. The data for analyzing the prevalence and heterogeneity of specific types of cancer was obtained from 13 studies of which 5 were from Karachi [ 1 , 6 , 7 , 15 ], 4 from Lahore [ 4 , 5 , 14 ], and 1 each from the Hazara Division in Khyber Pakhtunkhwa, Multan Division in Punjab, Larkana Division in Sindh, and Hyderabad Division in Sindh, respectively [ 2 , 3 , 9 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…A cancer surveillance programme, built around a PBCR, has a major role in informing the initial phases of a national cancer control plans, monitoring progress and evaluating the implementation of specific cancer control policies . Indeed, registry data have been central in assessing the magnitude of the cancer problem in support of the cancer control program in a number of countries in social and economic transition . Thailand launched its second NCCP in 2013 covering the period 2013–2017 .…”
Section: Discussionmentioning
confidence: 99%
“…[17][18][19] Indeed, registry data have been central in assessing the magnitude of the cancer problem in support of the cancer control program in a number of countries in social and economic transition. [20][21][22][23][24] Thailand launched its second NCCP in 2013 covering the period 2013-2017. 25 The NCCP comprises a number of interlinked strategies, including cancer informatics, primary prevention, secondary prevention, tertiary prevention and treatment, palliative care, as well as cancer control research and capacity-building.…”
Section: Discussionmentioning
confidence: 99%